The Internal and External Factors Competitiveness of Sinia. Co Coffee Shop in Lampung Province - Luluk Irawati; I Putu Ajie Windu Kertayoga; Muhammad Zaini (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This research aims to analyze internal and external factors that influence the competitiveness of Coffee at Sinia. Co. This research was conducted in Bandar Lampung. This location was chosen deliberately. The research period will be carried out from April to September 2023. In this research, informants were determined using purposive sampling with the judgment sampling category to answer problems related to internal and external factors. Respondents consisted of three people from the Sinia.Co Coffee Shop business and four academics in the agricultural socio-economic field whose research focus was related to competitiveness and coffee. Using a qualitative phenomenological research approach, this investigation seeks to explore a holistic view rather than dissect the individual components that comprise the whole. Sinia.Co Coffee Shop has built a strong presence in the coffee industry by leveraging these internal strengths. Affordable prices, distinctive taste, supporting facilities, and easy accessibility, the weaknesses consist of a limited menu, limited promotions, and brands that are not yet well known. In contrast, for external factors, the opportunities consist of the coffee-drinking lifestyle and developments in information technology, while The threats it faces consist of competitors and fluctuations in raw material prices.